Peranan Kepemimpinan Kepala Kamar Mesin dalam Meningkatkan Motivasi ABK - Adnan Adnan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aimed to determine the effectiveness of KKM in motivating engine crew members on ships and to find solutions to streamline the role of KKM leadership on ships. This research method is a qualitative research method based on an understanding of the role of the Head of the Engine Room (KKM) to motivate employees or crew in MV. Greenville 168. This study uses primary data, namely data obtained directly from respondents through interviews. The results of the study indicate that a harmonious relationship between leaders and subordinates in the work has been well established because the KKM is quite informative. However, harmonious relationships are still limited to work, while outside work they are not. The KKM's authority includes providing work instructions only based on habits that can lead to unclear duties and responsibilities. Therefore, it is necessary to build interpersonal relationships between KKM and machine crew members. The role as a monitor is further enhanced, especially the delivery of testimonials to companies so that the career path is more focused. In conclusion, the delegation of tasks should be documented not only based on habits that can cause estrangement with subordinates. Keywords: Head of Engine Room, Leadership, Motivation